Dialética formal - Assis, Sidney Geraldo Cota de (2025)
This research investigates formal dialectics as a structured method of debate. It aims to characterize this method and verify the feasibility of proposing a formalization of Brazilian legal discourse. To achieve this goal, both classical and contemporary models of formal dialectics are explored, with an emphasis on a practical application case related to legal discourse. The dissertation is divided into seven chapters, covering topics ranging from an introduction to argumentation theory to the proposal of a general model for formalizing legal dialogue. The classical models include the Socratic elenchus and medieval disputes (Obligationes). The Socratic Elenchus is described as a method of refutation aimed at exposing inconsistencies in the interlocutors' beliefs, while Obligationes are presented as medieval academic disputes that followed specific rules to test the consistency of opinions. The contemporary models correspond to the systems developed by Hamblin, Lorenzen and Lorenz, the pragma-dialectics of Van Eemeren and Grootendorst, and the adaptations made by Krabbe, Barth, and Walton. Hamblin's system is characterized by more flexible and permissive rules, while Lorenzen and Lorenz's system is more rigorous and structured. Van Eemeren and Grootendorst's pragma-dialectics propose a model of critical discussion aimed at resolving differences of opinion rationally. The adaptations by Krabbe, Barth, and Walton emphasize the importance of structured rules and the formalization of dialogue. The research concludes by highlighting the fundamental aspects of structured rules for resolving opinion conflicts in relation to the aforementioned theoretical frameworks. It also presents a proposal for formalizing Brazilian legal discourse through a set of rules, divided into propaedeutic and consecutive stages, covering the initiation of legal discourse, its execution, and the immutability of judicial decisions.